Identification of an autophagy-related 12-lncRNA signature and evaluation of NFYC-AS1 as a pro-cancer factor in lung adenocarcinoma - Tong, Fang; Xu, Lifa; Xu, Sheng; Zhang, Mingming (Frontiers in Genetics, 2022)
OBJECTIVE: To develop an autophagy related lncRNA-based risk signature and corresponding nomogram to predict overall survival (OS) for LUAD patients and investigate the possible meaning of screened factors. METHODS: Differentially expressed lncRNAs and autophagy genes were screened between normal and LUAD tumor samples from TCGA LUAD dataset. Univariate and multivariate Cox regression analysis were performed to construct the lncRNA based risk signature and nomogram incorporating clinical information. Then the accuracy and sensitivity were confirmed by the AUC of ROC curves in both training and validation cohorts. qPCR, immunoblot, shRNA and ectopic expression were used to verify the positive regulation of NFYC-AS1 on BIRC6. CCK-8, immunofluorescence and flow cytometry were used to confirm the influence of NFYC-AS1 on cell proliferation, autophagy and apoptosis via BIRC6. RESULTS: A 12-lncRNAs risk signature and a nomogram combining related clinical information were constructed. Furthermore, the abnormal increase of NFYC-AS1 may promote LUAD progression through the autophagy related gene BIRC6. CONCLUSIONS: 12-lncRNA signature may function as a predictive marker for LUAD patients and NFYC-AS1 along with BIRC6 may function as carcinogenic factors in a combinatorial manner.